Camarillo State Hospital Meeting of the Board of Trustees (1960)
This document is the agenda of which the meeting will consists of for the Board of Trustees. The meeting will take place in the Camarillo State Hospital on October 27, 1960. Dr. May will be leading this meeting in which topics such as new admission procedure, research programs, and admitting service will be discussed in order to make adjustments and improve the mental health program.